2020
DOI: 10.1002/phar.2480
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus intrapatient variability in solid organ transplantation: A multiorgan perspective

Abstract: Background Tacrolimus therapy in solid organ transplant (SOT) recipients is challenging due to its narrow therapeutic window and pharmacokinetic variability both between patients and within a single patient. Intrapatient variability (IPV) of tacrolimus trough concentrations has become a novel marker of interest for predicting transplant outcomes. The purpose of this review is to evaluate the association of tacrolimus IPV with graft and patient outcomes and identify interventions to improve IPV in SOT recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
48
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(58 citation statements)
references
References 78 publications
2
48
0
Order By: Relevance
“…It is classified as a narrow therapeutic index medication, displaying wide interpatient variability and intrapatient variability (IPV) and requiring frequent therapeutic drug monitoring of trough levels. [2][3][4][5] Therefore, it is critical to maintain therapeutic levels to preserve allograft function.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is classified as a narrow therapeutic index medication, displaying wide interpatient variability and intrapatient variability (IPV) and requiring frequent therapeutic drug monitoring of trough levels. [2][3][4][5] Therefore, it is critical to maintain therapeutic levels to preserve allograft function.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to assessing adequate trough levels, tacrolimus IPV is another important consideration for allograft longevity. 5 Increased tacrolimus IPV, as measured by coefficient of variation (CV%) or SD, is associated with deleterious outcomes in RT recipients, including increased allograft fibrosis, rejection, development of DSA, and decreased allograft survival. [5][6][7][8][9][10][11][12][13][14] Several studies assessing time in therapeutic range (TTR) with tacrolimus have demonstrated that patients with lower TTR values have been associated with de novo DSA (dnDSA) development and inferior allograft outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These physiopathological changes can be particularly marked in the pediatric context. In recent years, high intra-individual variability of TAC concentrations in WB was also described as significantly associated with the risk of graft rejection (Del Bello et al, 2018;Schumacher et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Tacrolimus is the mainstay of immunosuppression therapy and in recent years, intrapatient variability (IPV) in tacrolimus trough concentrations has become recognized as a novel marker to identify transplant recipients at risk for rejection and graft loss 15–17 . Schumacher et al 18 evaluated the association of tacrolimus IPV with patients and allograft outcomes and subsequently identified interventions to improve IPV in a systematic review. Pilch et al 19 provide readers with a broad description of the past, present, and future of immunosuppression in solid organ transplantation and sets the stage for how optimal long‐term outcomes can be achieved during the next era of transplantation with a focus on patient‐specific optimization over universal protocols.…”
mentioning
confidence: 99%